Commodifying magic: cyber shamans and neoliberalised culture in Korea. Issue 3 (2nd July 2016) - Lee, Joonseong
Abstract: This paper explores cyber shamans in the neoliberalised Korea. As new media technologies evolved, Korean shamans leaped at an opportunity of the new media technologies in ways to redeem themselves. I used the term 'redeem' here because historically shamans in Korea have been demonised by the ruling power for more than 500 years and therefore even in the modern times they were perceived as 'weird money suckers with false magic'. For this reason, the inherited dynamics of shamanism embedded in the culture were not appropriately considered. In the process of becoming cyber shamans, Korean shamans have cleverly utilised the new media and started making their presence known. Articulation of the inherited shamanic dynamic in response to the neoliberal media environment can help us to assess the various influences of the neoliberalised economic and political environment on Korean society.